ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NET EKSPOR DAN PERTUMBUHAN EKONOMI DI PROVINSI JAMBI - Putra, Sev Eka; Amar, Syamsul; Syofyan, Efrizal (Program Studi Magister Ilmu Ekonomi, 2014)
This study aims to analyze (1) Effect of consumption, investment, government spending and net exports to economic growth in Jambi and (2) Effect of production value, exchange rate, foreign income and net exports to economic growth in the province of Jambi. This research is a descriptive study and associative, while the data is the data type of the documentary, the data source is a secondary data as well as data in the form of time series of the first quarter of 2001 to the fourth quarter of 2010. This study using a simultaneous equations model analysis in the form of Two Stage Least Square (2 SLS). Endogenous variables in this study are economic growth and net exports. While the exogenous variables are consumption, investment, government spending, the amount of production, exchange rates and foreign income. The research concludes that (1) the consumption of a significant and positive impact on economic growth, investing a significant and positive impact on economic growth, government spending have a significant and positive impact on economic growth and net exports have a significant and positive impact on economic growth in the province of Jambi. If consumption increases, economic growth will also increase. If the increased investment, economic growth will also increase. If increased government spending, economic growth will increase. (2) Â production value and a significant positive impact on net exports, exchange rates have a significant and negative effect on net exports and economic growth have a significant and positive impact on net exports in Jambi Province. While foreign income is not significant and positive impact on net exports in Jambi Province. Keywords : Consumption, Investation, goverment spending, production, exchange rate, foreign income, net exsports and economic growt.